Pengaruh Loyalitas dan Fanatisme Supporter pada Klub terhadap Keputusan Pembelian Merchandise Orisinal: Studi pada Supporter Persela Lamongan - Asma'ul Khomsiyah; Sanaji Sanaji (Universitas Proklamasi 45 Yogyakarta, 2021)
This study aims to investigate the effect of loyalty and fanaticism on supporters’ loyalty in purchasing original merchandise. Fanaticism was proposed to mediate the effect of loyalty on purchase. About 100 samples from supporters of Persela Lamongan football club were used to test the proposed model. Data were collected by questionnaire and tested its validity and reliability. We apply Partial Least Square (PLS) method to test the hypothesis. Based on the research results, it could be concluded that fanaticism did not affect purchasing decisions. Meanwhile, it had been proven that supporter loyalty had a positive effect on fanaticism, supporter loyalty had a significant positive effect on purchasing decisions. It means that fanaticism was not able to strengthen the influence of supporter loyalty on purchasing decisions.